Cyclin-Dependent Kinase 5 Regulatory Subunit Associated Protein 3: Potential Functions and Implications for Development and Disease - Sheng, Linna; Li, Jiaxuan; Rao, Shengfang; Yang, Zhijun; Huang, Yonghong (Frontiers in Oncology, 2021)
Cyclin-dependent kinase 5 (CDK5) regulatory subunit associated protein 3 (CDK5RAP3, also named as C53 or LZAP) was initially identified as a binding protein of CDK5 activator p35. To date, CDK5RAP3 has been reported to interact with a range of proteins involved in cellular events ranging from cell cycle, apoptosis, and invasion to UFMylation modification and endoplasmic reticulum stress. Owing to its crucial roles in cellular processes, CDK5RAP3 is demonstrated to be not only an active participant in embryonic and mammalian tissue development, but also a key regulator in the onset and progress of human cancers such as head and neck squamous cell carcinoma, gastric cancer, hepatocellular cancer, lung cancer, kidney cancer and breast cancer. Notwithstanding, the detailed function of CDK5RAP3 and its mechanism remain poorly defined. Here, we briefly described a history of the discovery of CDK5RAP3, and systematically overviewed its gene structural and distribution features. We also focused on the known functions of this protein and its implications for embryogenesis and tissue development, as well as diseases especially carcinoma. This review may facilitate to understand the molecular and functional basis of CDK5RAP3 and its association with development and disease, and provide a reasonable idea for novel therapeutic opportunities targeting CDK5RAP3.